Analisis Performa Algoritma K-Means Clustering untuk Segmentasi Pasar di UMKM - Afrizal, Muhammad; Saputra, Ilham; Satria, Riyan; Rahmaddeni, Rahmaddeni (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the performance of the K-Means Clustering algorithm in market segmentation for Micro, Small, and Medium Enterprises (MSMEs). Using a quantitative approach, the data collected includes demographic information, purchasing behavior, and product preferences from respondents. The analysis process begins with data preprocessing, including normalization and outlier removal, before applying the K-Means algorithm to group customers into several segments. The performance evaluation of the algorithm is conducted using the Silhouette Score and Davies-Bouldin Index metrics. The analysis results indicate that the K-Means algorithm successfully identifies four distinct customer clusters, each with unique characteristics. The average Silhouette Score of 0.72 and a Davies-Bouldin Index of 0.45 suggest that the resulting clusters are well-defined and clearly separated. These findings provide valuable insights for MSMEs in formulating more effective and targeted marketing strategies.